(untitled) (Global Journal of Medical Research, 2024)
Introduction: It’s important to comprehend the key concepts of chronic ligament injuries to the ankle, which occur when there is deterioration or weakening and can result from recurrent or untreated trauma (AMODIO, 2013). Chronic ligament damage typically results from frequent ankle sprains. Ligaments are fibrous tissues that connect bones and provide stability for joints. In the ankle, the ligaments most commonly affected are the anterior talofibular ligament and the calcaneofibular ligament.